The Scanographic Profile Of Pancreatic Tumors In 3 Radiology Departments In Kinshasa - Antoine, Molua; Eric, Matondo; Michel, Lelo; Jean, Mukaya; Angele, Mbongo; StÃ©phane, Yanda; Bernard, Bazeboso; Mazoba, Tacite (Talenta Publisher, 2022)
Objective . Our objective was to describe the scanographic profile of pancreatic tumors in 3 radiology departments in Kinshasa. Methods . Comparative study conducted in 3 radiology departments in Kinshasa from January 2016 to June 2021, having retained 86 reports of abdominal CT-scans of patients with pancreatic pathology including 62 cases of pancreatic tumors. Results . Male patients were in the majority (sex-ratio M/F=1.6) with a mean age of 55.7Â±14.7 years (16 to 92 years). The frequency of pancreatic tumors was higher (62 cases/86) compared to that of inflammatory pathologies (20 cases/86). Cholestasis syndrome (50%) and abdominal (epigastric) pain were the most common indications. In tumors the contours were lobulated (56.1%) compared to pancreatitis, where they were blurred in 80% (p<0.05). In 45% of pancreatitis the peripancreatic fat was infiltrated, against 16.7% in tumors (p=0.01). The Wirsung duct was dilated in most tumors compared to pancreatitis where it was irregular with calcifications (p<0.05). The tumors were resectable in 26% of cases. Conclusion . The abdominal CT-scan contributes to the diagnosis of pancreatic pathologies. Tumors are the most common, most of them unresectable . It is often an elderly male subject with a clinical indication.